Effects of dietary marine sulphated polysaccharides (Algimun®) on growth performance, immune responses and disease resistance of juvenile gilthead seabream (Sparus aurata) to Photobacterium damselae subsp. piscicida - Güroy, Derya; Güroy, Betül; Bilen, Soner; Terzi, Ertuğrul; Kenanoğlu, Osman Nezih; García-Suárez, María; Marzin, Danièle; Mantoğlu, Serhan; Karadal, Onur; Şahin, İzzet; Kuşku, Halit (Elsevier BV, 2022)
The present study evaluated the effects of a dietary mix of marine sulphated polysaccharides, named Algimun® (AL), supplementation to gilthead seabream (Sparus aurata) juveniles in terms of growth performance, immune responses, and resistance against Photobacterium damselae subsp. piscicida. A total of 240 fish (initial mean weight of 6.00 ± 0.03 g) was randomly separated into 12 tanks (400 L, 20 fish per tank) distributed in four replicates. Fish were fed three experimental diets: a basal diet (Control), and a basal diet with two inclusion rates of Algimun® as 3 g/kg (AL0.3) and 5 g/kg (AL0.5) for 30 days before bacterial infection with P. damselae subsp. piscicida. After a 30-day feeding-period, growth performance was significantly improved in AL0.3 and AL0.5 groups compared to the control group (P < 0.05). AL0.3 and AL0.5 groups showed significantly higher lysozyme activity and myeloperoxidase activity when compared to the control group (P < 0.05). The gene expression of immune mediators (IL-1β, IL-6, IL-10, IL-18, TNF-α and COX-2) was significantly upregulated in the intestine, spleen and head kidney in AL0.3 and AL0.5 groups when compared to the control group (P < 0.05). Eight days post-challenge, the survival rate against P. damselae subsp. piscicida was numerically higher in fish within AL0.3 and AL0.5 groups compared to control (+20%). The study findings suggest that marine sulphated polysaccharides (Algimun®) could be used as an immunomodulator in gilthead seabream to support animal's health and boost resistance in case of disease outbreak.
Keywords: Fish Diseases; Photobacterium; Polysaccharides; Dietary Carbohydrates; Animals; Gram-Negative Bacterial Infections; Sea Bream; Disease Resistance; 14. Life underwater; 3. Good health